2002
DOI: 10.1095/biolreprod.102.006445
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Receptor Guanylyl Cyclase C and Its Ligands in Reproductive Tissues of the Rat: A Potential Role for a Novel Signaling Pathway in the Epididymis1

Abstract: Guanylyl cyclase C (GC-C) is a membrane-associated form of guanylyl cyclase and serves as the receptor for the heat-stable enterotoxin (ST) peptide and endogenous ligands guanylin, uroguanylin, and lymphoguanylin. The major site of expression of GC-C is the intestinal epithelial cell, although GC-C is also expressed in extraintestinal tissue such as the kidney, airway epithelium, perinatal liver, stomach, brain, and adrenal glands. Binding of ligands to GC-C leads to accumulation of intracellular cGMP, the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…This biochemical evidence for enteric production of Ugn has since been corroborated and extended by numerous Northern blot studies showing high and relatively selective expression of preproUgn mRNA in the intestine (2, 11, 19, 45, 49, 55-57, 67, 88). However, several of these Northern blot studies have also noted the presence of very low levels of preproUgn mRNA in the kidney, an observation that has been consistently confirmed by more sensitive RT-PCR assays (5,13,36,50). Here, we show that these low levels of renal mRNA are associated with an unexpectedly high abundance of proUgn polypeptide.…”
Section: Discussionsupporting
confidence: 80%
“…This biochemical evidence for enteric production of Ugn has since been corroborated and extended by numerous Northern blot studies showing high and relatively selective expression of preproUgn mRNA in the intestine (2, 11, 19, 45, 49, 55-57, 67, 88). However, several of these Northern blot studies have also noted the presence of very low levels of preproUgn mRNA in the kidney, an observation that has been consistently confirmed by more sensitive RT-PCR assays (5,13,36,50). Here, we show that these low levels of renal mRNA are associated with an unexpectedly high abundance of proUgn polypeptide.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies support the view postulated by Forte (16) that uroguanylin participates in an endocrine axis connecting the gastrointestinal tract with the kidneys in the regulation of body sodium balance (23,25,26). In addition, the GC-C receptor is expressed in the epididymis (27) and brain (28). Since guanylin, uroguanylin, and their cognate receptor GC-C are present in several body compartments, potential autoimmune reactions that interfere with GC-C-mediated signaling may have serious consequences.…”
mentioning
confidence: 55%
“…Somewhat surprisingly, this fundamental principle has not yet been established. Although Northern blot studies have shown that the small intestine is by far the major site for pre-proUGn mRNA expression (10,22,23), detectable amounts of pre-proUGn mRNA and/or immunoreactive UGn-like polypeptides have been reported in a variety of other tissues, including the kidney itself, as well as the colon, heart, stomach, lung, pancreas, brain, testis, ovary, oviduct, epididymis, prostate, parotid gland, submandibular gland, nasal mucosa, and gall bladder (10,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). One caveat to these studies is that the methods used have either been indirect (RNA based) or nonquantitative (immunocytochemical), and, where antibodies have been used, they have, for the most part, been unable to discriminate between UGn and proUGn.…”
mentioning
confidence: 99%